Central retinal vein occlusion in patients with metastatic solid tumors on tyrosine kinase inhibitors: a report of case series and literature review - Luo, Mingyue; Sun, Lu; Dai, Rongping; Chen, Youxin; Wu, Chan (Frontiers in Medicine, 2024)
Background Central retinal vein occlusion (CRVO) is a rare adverse effect related to the use of tyrosine kinase inhibitors (TKIs) in patients with metastatic malignancies, which has only been reported in several case reports. Case presentation We reported the case series of three CRVO patients on regular regimens of TKIs as part of targeted therapies for metastatic malignancies, all of whom were otherwise healthy with no or well-controlled systemic conditions. All these patients received injections of intravitreal dexamethasone implant (IDI) and achieved a fluid-free macula at the end of the visit. In addition, we reviewed the existing literature on this subject and present here an updated analysis of the related TKIs, ocular presentation, treatment, and prognosis. Conclusion All patients diagnosed with CRVO on TKIs received dexamethasone implant treatment and obtained a fluid-free macula. We would like to raise awareness among our colleague oncologists about the possibility of CRVO related to TKI use and the necessity for patients to be screened regularly by a retinal specialist.